A Comparative Study On Speaking Skill Between Extrovert And Introvert Students At The Second Grade Of SMAN 3 Bukittinggi - Nur Aisyah Merlin; Eliza (CV. Ulil Albab Corp, 2023)
The aims of this study were to know there was a difference between the extrovert and introvert students’ on their speaking skill and which one was better on speaking skill at the second grade students of SMAN 3 Bukittinggi. This research used descriptive quantitative method. The instrument of this research were questionnaire for classified the students based on their personality and speaking test for get their speaking score . The population was the second grade students at SMAN 3 Bukittinggi, meanwhile sample were 30 students who had been assigned purpossively. The finding showed; (1) There was difference between mean of extrovert students, which was (76.5) and the mean of introvert students, which was (82). (2)The result of ttes was -1,980 and it was smaller than ttable in the degree of significance 5% (2,048 > -1,980). The result showed that the students’ personality difference had no statistically difference to the students’ speaking skill. Based on the result of the research, the alternative hypothesis (Ha) was rejected and null hypothesis (Ho) was accepted. In conclusion there was no difference between extrovert and introvert students in speaking skill of the second grade students of SMAN 3 Bukittinggi.